Augmented Antitumor Activity for Novel Dual PI3K/BDR4 Inhibitors, SF2523 and SF1126 in Ewing Sarcoma. Issue 3 (April 2021) - Goldin, Amanda N.; Singh, Alok; Joshi, Shweta; Jamieson, Christina; Durden, Donald L.
Abstract : Ewing sarcoma (ES) is the second most common pediatric bone cancer. Despite recent advances in the treatment, patients with metastatic tumors have dismal prognosis and hence novel therapies are urgently needed to combat this cancer. A recent study has shown that phosphoinositide-3 kinase (PI3K) inhibitors can synergistically increase sensitivity to bromodomain and extraterminal domain inhibitors in ES cells and therefore combined inhibition of PI3K and bromodomain and extraterminal domain bromodomain proteins might provide benefit in this cancer. Herein, we have investigated the efficacy of dual PI3K/BRD4 inhibitors, SF2523 and SF1126, for their antitumor activity in ES cell lines. The effect of SF1126 and SF2523 on cell viability and PI3K signaling was assessed on a panel of human ES cell lines. To evaluate the antitumor activity of SF1126, A673 cells were injected intrafemorally into RAG-2−/− mice and treated with 50 mg/kg SF1126 6 days per week, for 30 days. Both SF1126 and SF2523 decreased cell survival and inhibited phosphorylation of AKT in human ES cell lines. In vivo, SF1126 showed a significant reduction in tumor volume. These results suggest that dual PI3K/BRD4 inhibitor, SF1126, has antitumor activity in ES models.